Association between Cigarette Smoking and Occupational Noise Exposure on Hearing Loss and Hearing Impairment - Rahimpour F, Mirzamohammadi E, Attarchi MS, Mohammadi S (Babol University of Medical Sciences, 2011)
BACKGROUND AND OBJECTIVE: Noise induced hearing loss (NIHL) is one of the most common occupational diseases. The basis of hearing impairment may be a combination of mechanical and metabolic factors. Since many causes of hearing loss are preventable. The main goal of study was to assess the effect of cigarette smoke on hearing impairment and occupational noise induced hearing loss.METHODS: This cross-sectional study was conducted on 439 workers of a large home appliances factory in vicinity of Tehran that exposed to noise levels exceeding 85 dB. Required data were obtained by direct interview and audiometric test (PTA-Pure Tone Audiometry). Workers were divided into two groups of smokers and non-smokers. The hearing loss was compared in two groups based on two models. In model 1, the hearing threshold differences was higher than 30 dB between 4000 and 1000 Hz and in model 2, hearing threshold level was higher than 25 dB at 4000 Hz.FINDINGS: The frequency of hearing loss in smoker workers was higher than non smokers. Based on model 1: Odds Ratio: 10.29, p<0.001 and CI95%: 4.86-21.8 and based on model 2: Odds Ratio: 5.07, p<0.001and CI95%: 3.19-8.07). In addition in our study hearing impairment was significantly higher in smokers than non-smokers (Odds Ratio: 4.14, CI95%:1.29-13.27, p< 0.01).CONCLUSION: It can be concluded that smoking may accelerate NIHL and hearing impairment, so establishment of educational courses of smoking cessation in workplaces may be a useful method to decrease the severity of noise induced hearing loss and hearing impairment in workers.